The behavior pattern of parents of patients with subacute sclerosing panencephalitis concerning alternative medicine - Sedat Işıkay (The Turkish Journal of Pediatrics)
The aim of the study was to examine the attitude of the parents of Subacute Sclerosing Panencephalitis (SSPE) patients regarding alternative treatment methods and compare with those of the parents of epilepsy patients. The study comprised 39 SSPE and 53 epilepsy patients who were under follow-up in Gaziantep Children`s Hospital. A questionnaire designed to inquire about the knowledge (13 questions) and behavior (11 questions) of parents about alternative medicine methods was given to the caregiver of all patients. The ratio of parents using alternative medicine methods was 29/39 (74.4%) in the SSPE group and 8/53 (15.1%) in the epilepsy group. Less than half of the parents of SSPE patients reported talking about it with their doctors. These results show parents facing a chronic debilitating disease frequently seek benefit from alternative methods. Most define this treatment as complementary to the established medical treatment. However, potential and unrecognized adverse events of alternative methods and their interference with regular medical treatment can be of importance, especially because treating physicians are seldom informed about concurrent use.